2007
DOI: 10.1111/j.1526-4637.2007.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Iowa Pain Thermometer and Other Selected Pain Intensity Scales in Younger and Older Adult Cohorts Using Controlled Clinical Pain: A Preliminary Study

Abstract: Based on sensitivity to change, lower failure rates, higher preference evaluations, and little appreciable affects associated with cognitive impairment, the IPT was judged to be the best choice for assessing pain intensity for both age cohorts and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 56 publications
2
133
0
10
Order By: Relevance
“…Studies have shown that the IPT is reliable, valid, and generally preferred over other pain intensity tools (Herr et al, 2007;Taylor, Harris, Epps, & Herr, 2005;Ware, Epps, Herr, & Packard, 2006). In addition, Herr et al (2007) reported that the IPT had the lowest failure rate when compared with four other pain intensity tools in a sample of older adults, 22% of whom were cognitively impaired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the IPT is reliable, valid, and generally preferred over other pain intensity tools (Herr et al, 2007;Taylor, Harris, Epps, & Herr, 2005;Ware, Epps, Herr, & Packard, 2006). In addition, Herr et al (2007) reported that the IPT had the lowest failure rate when compared with four other pain intensity tools in a sample of older adults, 22% of whom were cognitively impaired.…”
Section: Methodsmentioning
confidence: 99%
“…Pain intensity was measured using the Iowa Pain Thermometer (IPT), which incorporates a vertical visual scale (a graphic representation of a thermometer that becomes increasingly red as pain intensity increases), verbal descriptors, and numeric methods for scoring pain intensity (Herr, Spratt, Garand, & Li, 2007). Verbal descriptors of pain range from no pain at the base of the thermometer to the most intense pain imaginable at the top.…”
Section: Methodsmentioning
confidence: 99%
“…19 Patients are more familiar with the VNRS, which is commonly used in clinical practice to assess pain intensity. 20 Preference. Patients' preference regarding HFCWO and CPT was measured by using an abridged version of the Chest Physiotherapy Satisfaction Survey developed by Oermann and colleagues.…”
Section: Methodsmentioning
confidence: 99%
“…Designed for children aged 3 years and over, the FPS-R is also helpful for elderly patients who may be cognitively impaired (35,46,47) (43,44). It has been shown that older patients prefer thermometer scales considering them to be the easiest to understand, and these are recommended by national and international guideline panels (43,48,49). Patients are shown the scale and asked to think that pain increases as you move to the top of the scale in the same way as temperature rises in a thermometer.…”
Section: Reviewmentioning
confidence: 99%
“…This scale uses descriptive anchors spaced along its length, with the spacing of the descriptor representing logarithmic changes in pain intensity. The Pain Thermometer aligns a thermometer alongside the words representing different levels of pain severity (43) (Fig. 2).…”
Section: Reviewmentioning
confidence: 99%